Development and Evaluation of a Novel Patient-Reported Outcome Implementation Process in a Student-Led Pro Bono Clinic: Acceptability and Adoption. Issue 3 (4th September 2021) - Staples, Trevor; Beran-Maryott, Gillian; Brinkerhoff, Alan; Bradford, Misha; Ward, R. Scott; Thackeray, Anne
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background and Purpose: Although patient-reported outcomes (PROs) are increasingly implemented to inform care and demonstrate the value of care across disciplines and settings, no previous reports have assessed PRO implementation and acceptability to student clinicians in a pro bono physical therapy clinic. The purpose of this case report was to describe the development and evaluation of an implementation process for an electronically administered PRO in a pro bono physical therapy clinic. Case Description: A student-faculty team used the consolidated framework for implementation research to identify barriers to PRO implementation in one student-run pro bono clinic and develop strategies to address identified barriers. The change management theoretical framework was used to develop an implementation process that addressed all general and local contextual needs. Acceptability and adoption of the Patient-Reported Outcome Measurement Information System Physical Function (PROMIS PF) computer adaptive test to student clinicians were assessed to evaluate implementation effectiveness. Outcomes: Implementation barriers included rotating student teams, limited knowledge, need for workflow modifications, and PRO translation to Spanish. Student clinician training, workflow adaptation, and use of English and Spanish versions of PROMIS PF addressed all barriers, general and local contextual needs. Student clinician responses suggested that implementation strategies were acceptable, citing increase efficiency and simplicity. Patient-Reported Outcome Measurement Information System Physical Function adoption was 81% (per month range = 47–100%) over the 6-month implementation period. Discussion and Conclusion: Acceptance and adoption rates by student clinicians indicate that implementation of PROMIS PF was successful at improving PRO collection and influencing student clinician education about PROs.